Wine consumers' willingness to adopt environmentally friendly packaging practices at tasting rooms: An ECHAID analysis. Issue 1 (24th September 2019) - Kelley, Kathleen; Bruwer, Johan; Zelinskie, Jennifer; Gardner, Denise; Govindasamy, Ramu; Hyde, Jeffrey; Rickard, Bradley
Abstract : Purpose: The purpose of this paper is to investigate consumers' wine preferences, recycling attitudes and behaviors and socio-demographic data in an effort to build market segment profiles of those willing to transport wine bottles back to winery tasting rooms to be recycled, interest in standard-weight glass-alternative packaging and, various cork-alternative bottle closures. Design/methodology/approach: A two-stage online survey was administered to 714 wine consumers residing in the Mid-Atlantic region of the USA during two periods in March 2016. Exhaustive chi-square automatic interaction detector (ECHAID) decision tree predictive analysis was used to identify the market segments. Findings: A majority of survey participants were willing to bring empty wine bottles to a winery for recycling (85 percent). Collectively, 77 percent of participants were members of just three of the eight segments developed using a decision tree predictive algorithm, with 90 percent of participants in these segments willing to bring empty wine bottles to a winery tasting room to be recycled. Two segments were comprised of Millennials and Generation X, and the third of Baby Boomers, two having a moderate to extreme interest in natural cork used to seal wine bottles, and similar. Originality/value: An ECHAID classification tree method was used to develop eight consumer segments. Identifying characteristics that describe consumers likely to return empty wine bottles to a winery benefits recycling efforts and could possibly encourage additional sales.